Análise crítica do papel da vítima nos crimes cibernéticos e dos desafios do controle penal - Sousa, Lucas Queiroga Nóbrega de (2023)
In the face of a growing societal dependence on digital systems, cybercrimes have increased in frequency and complexity in the contemporary era. This study aimed to analyze the main categories influencing the participation and vulnerability of victims in the commission of cybercrimes, establishing a connection with the challenges faced in the application of criminal control in this reality. The research explored the effects of technological development on user autonomy, followed by an analysis focusing on the victimological bias of Bernd Schunemann. Subsequently, the enigma of risk in the virtual world was examined, referring to moderate functionalist theories such as Claus Roxin's. This was followed by philosophical and theoretical analyses by Zygmunt Bauman, Pierre Lévy, and Andy Clark regarding the complexity of this theme in contemporary times. The study also sought to analyze the significant role of the victim in the crime from a doctrinal perspective, and subsequently, the research focused on discussing the impacts generated by the vulnerability of the victim in dissonance with the normative evolution of cybercrimes, highlighting persistent challenges in the realm of criminal control and perpetrator identification. The investigation then delved into possible strategies for preventing and combating these crimes. The methodology adopted was based on a logical-deductive approach, involving bibliographical and documentary analyses. Additionally, risk mitigation measures were examined to strengthen cybersecurity and reduce the occurrence of cybercrimes, contributing to the discussion of current criminal policy strategies in controlling this growing form of criminality.